Corruption as an anathema to human rights laws and practice in Nigeria (2019)
Corruption. though a universal phenomenon. its menace in Nigeria is alarming as it pervades through every strata of the society with its huge adverse effects on the populace. Over the years. the incidence of corruption has grown to become a 'norm' in Nigeria, with the nation becoming a pariah state in the comity of nations. However. the practice is widely considered to have greater impact on the nation compare to its citizens, it is therefore justifiably domiciled under the Nigerian Criminal Law usually as an offence to be prosecuted by the state on behalf of its citizens. This paper therefore considers the impact/effect of both private and public corruption on the Human Rights Laws and Practice in Nigeria, with emphasis on analysis of corruption as a violation of the entrenched rights of citizens. Critical issues such as legal framework for human rights and various anti-corruption laws were examined. It is observed that successive governments in Nigeria are usually blamed for economic woes and decay in infrastructure, often attributed to incompetence and negligence while its agencies, such as Police Force. Armed Forces. banks. private persons who are active collaborators are often over-looked. The paper therefore concluded that the impact of corruption could only be holistically measured by the rate of violations of the citizens' rights as provided for by the law and same made punishable. It is further submitted that such infringement on the right of persons occasioned by corrupt practices should not only be tried as abuse of rights but also attract some form of compensation for the victims.